if (x+4)(x+1)-(x-1)(x-2)=0 find the value of x
Answers
Answered by
12
Questions:-(x+4)(x+1)-(x-1)(x-2)=0
Solution:-
![( {x}^{2} + x + 4x + 4) - ( {x}^{2} - 2x - x + 2) ( {x}^{2} + x + 4x + 4) - ( {x}^{2} - 2x - x + 2)](https://tex.z-dn.net/?f=%28+%7Bx%7D%5E%7B2%7D+%2B+x+%2B+4x+%2B+4%29+-+%28+%7Bx%7D%5E%7B2%7D+-+2x+-+x+%2B+2%29)
![( {x}^{2} + 5x + 4) - ( {x}^{2} - 3x + 2) ( {x}^{2} + 5x + 4) - ( {x}^{2} - 3x + 2)](https://tex.z-dn.net/?f=%28+%7Bx%7D%5E%7B2%7D+%2B+5x+%2B+4%29+-+%28+%7Bx%7D%5E%7B2%7D+-+3x+%2B+2%29)
![{x}^{2} + 5x + 4 - {x}^{2} - 3x + 2 {x}^{2} + 5x + 4 - {x}^{2} - 3x + 2](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+%2B+5x+%2B+4+-+%7Bx%7D%5E%7B2%7D+-+3x+%2B+2)
2x+6=0
x= -3
Solution:-
2x+6=0
x= -3
Answered by
2
Answer:
-1/4
Step-by-step explanation:
(x²+4x+X+4)+(-x²+2x+x-2)
x²-x²+4x+2x+X+X+4-2
6x+2x+2=0
8x = (-2)
X = (-1/4)
Similar questions